Impact of Shariah Compliance on Financial Performance of Islamic Banks: Evidence from Pakistan - Javed, Muhammad Mansoor; Syed Muhammad Hassan Bukhari; Adnan Bashir (Islamic Banking and Finance Review, 2022)
Despite the remarkable growth of the Islamic banking industry over the past few decades, its Shariah legitimacy is still debated. In this regard, most of the pronouncements of Shariah scholars are deduced from secondary sources of Islamic jurisprudence which are open to diverse interpretations. In general, the well-known Islamic legal maxim “Al-Kharaj bil Dhaman” suggests that each Shariah compliant business should be exposed to some kind of risk. Arguably, while pursuing the goal of profit maximization, Islamic banks offer such risk free modes of financing that undermine their Shariah legitimacy. In this context, some studies explored the relationship between Shariah compliance and profitability. These studies mostly reported mixed findings because they measured Shariah compliance using irrelevant or limited proxies. In light of these findings, the purpose of the current study was to revisit this relationship by applying a more comprehensive proxy to measure Shariah compliance of Islamic banks. To this end, it analyzed unbalanced panel data extracted from the annual reports (2008-2020) of five full-fledged Islamic banks operating in Pakistan. Applying the robust fixed effect model, it found a significant positive relationship between Shariah compliance and financial performance, suggesting that better Shariah compliance leads to improved financial performance.